PENGEMBANGAN MEDIA MONTASE ( MENYUSUN POTONGAN GAMBAR ) PADA PEMBELAJARAN IPA MATERI BENTUK DAN FUNGSI BAGIAN TUMBUHAN UNTUK SISWA KELAS IV SD NEGERI MOJOROTO 4 KABUPATEN KEDIRI - Nofitasari Mustika Rahayu; Sutrisno Sahari; Agus Widodo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to determine the validity, practicality and effectiveness of developing montage media in science learning material on the form and function of plant parts in class IV Mojoroto State Elementary School 4. This type of research uses the development method (Research and Development) with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), with research subjects being teachers and students of class IV at SD Negeri Mojoroto 4, while the data collection instruments were in the form of observations, questionnaires and questions, then validation was carried out by material experts, media experts and practitioners. Data analysis techniques use qualitative descriptive and quantitative descriptive. The results of the development of this media are (1) The validity of the montage media obtained from media experts is 86% and material experts 84%, the category is very valid and suitable for use in research. (2) The practicality of montage media from teacher responses obtained 88% who received positive responses and strongly agreed to be used for research. Likewise, student responses during limited and extensive trials were 85% and 97% good responses to the media. (3) The effectiveness of montage media in completing classical learning during limited and extensive trials was categorized as very effective by obtaining 82% and 100% completion in the questions. Based on the results obtained, the montage media developed was declared valid, practical and effective, making it suitable for use in supporting the learning process.